Adaption of distance learning to continue the academic year amid COVID-19 lockdown. (July 2021) - Qazi, Atika; Qazi, Javaria; Naseer, Khulla; Zeeshan, Muhammad; Qazi, Shiza; Abayomi-Alli, Olusola; Said Ahmad, Ibrahim; Darwich, Mohammad; Ali Talpur, Bandeh; Hardaker, Glenn; Naseem, Usman; Yang, Shuiqing; et al.
Highlights: The study aims to investigate the use of distance learning in saving students' academic year amid COVID-19 lockdown. Trust in information sources influence the adoption of distance learning. Situational awareness and readiness contribute to adopting distance learning amid the COVID-19 pandemic. Abstract: This work investigates the use of distance learning in saving students' academic year amid COVID-19 lockdown. It assesses the adoption of distance learning using various online application tools that have gained widespread attention during the coronavirus infectious disease 2019 (COVID-19) pandemic. Distance learning thrives as a legitimate alternative to classroom instructions, as major cities around the globe are locked down amid the COVID-19 pandemic. To save the academic year, educational institutions have reacted to the situation impulsively and adopted distance learning platforms using online resources. This study surveyed random undergraduate students to identify the impact of trust in formal and informal information sources, awareness and the readiness to adopt distance learning. In this study, we have hypothesized that adopting distance learning is an outcome of situational awareness and readiness, which is achieved by the trust in the information sources related to distance learning. The findings indicate that trust in information sources such as institute and media information or interpersonal communication related to distance learning programs is correlated with awareness (β = 0.423, t = 12.296, p = 0.000) and contribute to readiness (β = 0.593, t = 28.762, p = 0.001). The structural model path coefficient indicates that readiness strongly influences the adoption of distance learning (β = 0.660, t = 12.798, p = 0.000) amid the COVID-19 pandemic. Our proposed model recorded a predictive relevance (Q 2 ) of 0.377 for awareness, 0.559 for readiness, and 0.309 for the adoption of distance learning, which explains how well the model and its parameter estimates reconstruct the values. This study concludes with implications for further research in this area.